ISLAMIC EDUCATION AND DECENTRALIZATION OF GOVERNMENT : Study of Local Government Policy in the Implementation of Islamic Religious Education in Indonesia - Ismail, Ismail; Fauzi, Ahmad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
Changes in the government management system in Indonesia from centralized to decentralized have changed the way people perceive local government authority in the management of Islamic education. Although Islamic education in general, and madrasas in particular have not become the object of regional autonomy, at least the community hopes that local governments will use this decentralized moment as an entry point to participate in the implementation of Islamic religious education. This research is a library research, in which documents as a source of data can be obtained either directly or through internet browsing. The results of this study include: (1) the regional government issued a policy to take part in the implementation of Islamic religious education; (2) the form of regional government policies in the implementation of Islamic religious education consists of: regional regulations (provincial/regency/city perda), regional head regulations (Pergub/Perbup/Perwali), and development activity programs; (3) the substance of regional government policies in the delivery of Islamic religious education targets the education curriculum/material, teacher competence, educator welfare, and educational infrastructure.